PENGARUH TERAPI BIRTH BALL TERHADAP INTENSITAS NYERI PERSALINAN KALA I PADA IBU BERSALIN DI PMB NENG TUTI ALAWIYAH BOGOR: PENGARUH TERAPI BIRTH BALL TERHADAP INTENSITAS NYERI PERSALINAN KALA I PADA IBU BERSALIN DI PMB NENG TUTI ALAWIYAH BOGOR - Riya Tanzilatun Amillah; Rani Safitri; Raden Maria Veronika Widiatrilupi (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2024)
Introduction: Labor pain is physiological in the process of labor with different pain intensities in each individual and disappear. Nonpharmacological methods tend to be easier and safer to give to laboring mothers, one of the methods is birth ball. Birth ball is a physical therapy ball that helps the progress of labor in laboring mothers in the opening stage. The purpose of this study was to determine the effect of birth ball therapy on the intensity of labor pain during the first stage in laboring mothers at PMB Neng Tuti Alawiyah Bogor. Method: This type of research used in this study is quantitative research using the Quasi Experiment research method in one group (one group pre test post test). Results: The results of statistical tests measuring the intensity of labor pain during the first stage in laboring mothers both before and after intervention using birth ball therapy obtained a p-value of 0.000 (p-value <0.05 at α = 5%). Conclusion: It can be concluded that the use of birth ball therapy is effective on the intensity of labor pain during the first stage in laboring mothers at PMB Neng Tuti Alawiyah Bogor